Is 18 F-fluorodeoxyglucose-positron emission tomography or computed tomography scan a triaging technique for axillary dissection in breast cancer? - Krishnaswamy, Uma; Vasantham, Sai Sampath Kumar; Kumar, Yasvanth (International Surgery Journal, 2023)
Background: To determine if fluorodeoxyglucose-positron emission tomography/ computed tomography (FDG PET/CT) scan identifies axillary nodal disease in conjunction with ultrasound (US) guided fine needle aspiration cytology (FNAC) of suspicious axillary nodes in breast cancer. To determine if this will enable axillary node dissection upfront, avoiding sentinel lymph node biopsy (SLNB). Methods: Study was performed in Apollo main hospital, Off Greams-lane, Greams road, Chennai IRB approval was obtained from institutional ethical committee-bio medical research-Apollo hospitals, (IEC application number: AMH-C-S-029/04-23). Informed consent was obtained from all the patients who met the inclusion criteria. The 61 patients with cT1-T3, N0-N1, and M0 disease underwent 18F-FDG-PET/CT scans after mammographic evaluation and an US guided FNAC of nodes which were seen to be suspicious in the mammogram and correlated US of the Axilla. All patients underwent axillary lymph node dissection (ALND levels 1 and 2) without a SLNB. Results: Out of 61 patients, 40 (65.6%) had axillary node uptake on PET/CT scan. But, after ALND, only 32 patients were found to have metastatic nodes on the histopathological examination (HPE) of the operative specimen. Out of these 32 patients, results for axillary metastasis had been noted on PET/CT, US, and guided FNAC in 18 patients (56.3%). Discordant results were noted in 14 (43.8%) patients, 29 patients had no metastasis on HPE. Negative results for axillary metastasis were noted on PET/CT, US and guided FNAC in 26 patients (89.7%). The results were discordant in 3 (10.3%) patients. Conclusions: An expanded preoperative axillary assessment does not have sufficient reliability to serve as a reliable triaging technique in axillary management. Concordant positive results may permit directly proceeding to ALND without resorting to SLNB. Concordant negative results may similarly permit avoiding axillary surgery. But discordant results warrant SLNB for assessment of axilla.